Laboratory course on fundamentals of nuclear physics: study aid; учебно-методическое пособие - Ryzhakova (Rizhakova) N. K. Nadezhda Kirillovna; Rogova N. S. Natalya Sergeevna; Verkhoturova V. V. Vera Viktorovna; Cherepennikov Yu. M. Yuriy Mihaylovich (Tomsk, TPU Publishing House, 2022)
Title screen